Evaluasi Kepuasan Peserta terhadap Pelatihan Artificial Intelligence (AI) dalam Mendukung Penguatan Literasi Digital Siswa Sekolah Menengah - Yeyendra Yeyendra; Ibnu Hajar; Hengki Satria; Putri Amelia; Mitra Yuwita (CV. ITTC INDONESIA, 2026)
Artificial Intelligence (AI) training has become an important strategy for strengthening students' digital literacy and preparing them to face rapid technological advancement. The success of a training program is not only determined by participants' learning outcomes but also by their satisfaction with the quality of the program implementation. This study aimed to evaluate participants' satisfaction with an Artificial Intelligence (AI) training program designed to strengthen digital literacy among students at SMAN 1 Batang Cenaku. A descriptive quantitative survey approach was employed involving 32 students who participated in the training program. Data were collected using a participant satisfaction questionnaire consisting of eleven evaluation indicators, including the relevance of training materials, quality of presentation, facilitator services, perceived benefits, and overall satisfaction. The data were analyzed using descriptive statistics, including mean scores, percentages, and the Participant Satisfaction Index (PSI). The results indicated that all evaluation indicators were classified as Very Satisfied, with an average PSI of 95.65%. The highest score was obtained for overall participant satisfaction (99.22%), while the lowest score was found for the facilitator service indicator (90.63%), which was still categorized as very satisfied. These findings indicate that the AI training program was implemented effectively and successfully met participants' learning needs. Therefore, this training model can be recommended as an effective community engagement program for strengthening digital literacy among secondary school students.